1999
DOI: 10.1016/s0022-5347(01)61789-0
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment of Vasomotor Symptoms in Men With Prostatic Carcinoma: A Pilot Study

Abstract: Background: Most men who undergo castration therapy due to prostatic carcinoma will suffer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 46 publications
1
59
0
1
Order By: Relevance
“…There is increasing evidence for its effect on vasomotor symptoms in non-cancer patients, [47][48][49] and cancer patients. [50][51][52][53][54][55][56] It is effective for patients troubled by xerostomia, [57][58][59] including those who have had radiotherapy and whose symptoms are not improved by pilocarpine.…”
Section: Scientific Background To Acupuncturementioning
confidence: 99%
“…There is increasing evidence for its effect on vasomotor symptoms in non-cancer patients, [47][48][49] and cancer patients. [50][51][52][53][54][55][56] It is effective for patients troubled by xerostomia, [57][58][59] including those who have had radiotherapy and whose symptoms are not improved by pilocarpine.…”
Section: Scientific Background To Acupuncturementioning
confidence: 99%
“…84 Of the 6 men who completed the study, 70% reported fewer symptoms compared to baseline at 10 weeks, and 50% reported fewer symptoms 3 months after the therapy ended. While this study had no control group, the results were interesting.…”
Section: Flushingmentioning
confidence: 90%
“…Three prospective uncontrolled cohort studies have been completed, one in men who had undergone castration for prostate cancer, and two in women who were taking tamoxifen for breast cancer. All demonstrated a reduction in vasomotor symptoms [309][310][311] . Prolonged stimulation using semi-permanent studs or needles, especially at SP6 appears to be associated with more long-term relief of symptoms 270 .…”
Section: Acupuncturementioning
confidence: 98%